Strategi Optimalisasi Pelayanan Sirkulasi Dengan Pendekatan Model Harapan Sosial: Studi Pada Perpustakaan UNRI Pascagangguan Alam - Ajir Ajir; Evi Susanti; Yasin Setiawan (Perpustakaan Universitas Riau, 2022)
This study aims to find out the description of optimizing circulation room repairs after infrastructure damage due to natural disturbances. This research uses the Research And Development (R&D) method. This analytical method is widely used in research to develop an innovative product, including it can be used in optimizing circulation services. Technically, this concept is a development research methodology conducted at the CRDS (Center for Research and Development Strategy) in Japan. A brief description of this concept is the research stages depicted through the diagram